A Public Health Issue: Dietary Supplements Promoted for Brain Health and Cognitive Performance - Crawford, Cindy (J Altern Complement Med, 2020)
Background: Dietary supplements targeting brain health have quickly emerged in the marketplace as cognitive performance becomes an important public health issue. While manufacturers are required to report the exact ingredients and formulations listed on the Supplement Facts labels of products, many reports have indicated such labels are not always truthful, and the content of some products is inconsistent with the ingredients listed on the Supplement Facts label. Objectives: To identify dietary supplement products and ingredients marketed for brain health and cognitive performance and perform analyses of select products to verify whether purported claims are truthful and product labels accurate. Design: A scoping review was performed to identify products and ingredients. Products were selected for content analysis, investigated for scientific-sounding claims made, and assessed using an educational tool for potential red flags when reading Supplement Facts labels. Results: Twelve products were selected from the 650 products being marketed for brain health and queried about by Service Members. Eight (67%) had at least one ingredient listed on the Supplement Facts label not detected through analysis. Compounds not reported on the label were detected in 10 (83%) products. Scientific-sounding claims made are not supported by science and red flags are presented. Conclusions: There are dietary supplements targeting brain health being marketed to consumers that should be considered adulterated and misbranded. Advertisements and product labels may be deceiving and could put the public at risk. Education is required so that the public can recognize red flags while the U.S. Food and Drug Administration works to “modernize” the current regulations for dietary supplements.